ENHANCING THE SAFETY OF FOREIGN WORKERS THROUGH LANGUAGE DEVELOPMENT AND THE COMPETENT USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTS) - Iis Kurnia Nurhayati; Alila Pramiyanti; Yuliani Rachma Putri (Jurnal Sosioteknologi, 2017)
The focus for this research was how the knowledge of a foreign language and the competence in the use of information and communication technologies (ICTs) contributed to the safety of Indonesians working abroad. The study was questionnaire-based research and semi-structured interviews with Indonesian workers working in the informal sectors, particularly as domestic workers in Singapore, Taiwan, Malaysia and Hongkong. The method led to rich correlational and qualitative data providing an in"depth understanding of how knowledge of a language and competence on information and communication technologies contributed to the safety of Indonesians in these countries. Thus, the results provided here have proved the usefulness of understanding different languages and also the benefit of being competent on the use of cellular phones as one of the examples of information and communication technology. This research provides a basis for suggesting areas where recruiting companies can intervene to ensure safety while working over-seas.